Effectiveness of the SISUMAKER Application Implementation in Electronic Archive Management at the Regional Office of the Ministry of Law and Human Rights of West Sumatra: Efektivitas Penerapan Aplikasi dalam Pengelolaan Arsip Elektronik di Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Sumatera Barat - Pratiwi, Laras Putri; Aldri Frinaldi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study aims to analyze Effectiveness of The SISUMAKER Application Implementation in Electronic Archive Management at the Regional Office of the Ministry of Law and Human Rights of West Sumatra. This type of research is qualitative, using the Manual Data Analysis Procedure (MDAP) technique. The results of this study indicate that the analysis from several aspects for The Effectiveness Of SISUMAKER Application Implementation In Electronic Archive Management At The Regional Office Of The Ministry Of Law And Human Rights Of West Sumatra includes, from the aspect of adaptation, most employees are able to use the SISUMAKER application, but some employees in UPT are still unable to utilize it. Then, from the aspect of integration, the SISUMAKER application is effectively integrated into each division. From the aspect of motivation, the SISUMAKER application greatly facilitates employees in the process of distributing or disposing of incoming and outgoing letters. Lastly, from the aspect of production, incoming and outgoing letters, as well as other archives, are managed effectively and efficiently but sometimes encounter obstacles due to network and system issues from the central office. The obstacles encountered in the implementation of the SISUMAKER application include occasional problems from the central system or the Data and Information Center (PUSDATIN), facilities and infrastructure experiencing damage or not functioning properly, a lack of features that hinder the process of managing incoming and outgoing letters, a lack of understanding among some employees in utilizing the SISUMAKER application, and some employees who are not competent in using the application. Finally, the solutions undertaken to improve the effectiveness of the SISUMAKER application implementation include providing guidance and monitoring in the use of the application at each UPT, maintaining and strengthening the application system and improving facilities and infrastructure, proposing the addition of features to PUSDATIN that are deemed necessary to expedite the management of incoming and outgoing letters on the SISUMAKER application, and conducting quarterly surveys on the effectiveness of the SISUMAKER application usage.